Search-based advertising and revenue management - Özlük, Özgür (Henry Stewart Talks, 2009)
What is online advertising?, Revenue management questions in online advertising, Online advertising from publisher's perspective, Online advertising from advertiser's perspective, Basic analytical models, Research findings of practical interest